Comparing selected types of aggressiveness and individual types of hostility among students of sports hockey classes - Görner, K.; Greganova, M.; Wojcik, K.; Spieszny, J. (Journal of Kinesiology and Exercise Sciences, 2018)
Aim of the research was to find out and compare individual subsystems of selected types of aggressiveness and individual types of hostility within age categories of learners of sports hockey classes. Research sample consisted of sixth, seventh, eighth and ninth grade boys from primary schools. Age of learners varied from 11 to 14 years. Total sample consisted of 120 learners. The research was it was implemented with the help of a standardized psychological questionnaire B - D - I. In the results we`re comparing the differences in individual subspecies of aggressive behaviour and also in overall aggressiveness between younger and older learners grade. It turned out that in all of the observed comparisons older learners achieved higher average values of the weighted score than younger. The difference was confirmed also by the nonparametric Mann Whitney U test, which at the unilateral test of 5 % level of demonstrability tells that between younger and older learners there`s statistically significant difference p = 0.031. Also, any increased value of the resentment didn`t occur neither among younger learners who achieved the average value of the weighted score 4.19 nor among older learners with the average value of the weighted score 4.81 and therefore there is not statistically significant difference (p = 0.681). Our research revealed that controlling emotions such as aggression is very important. Therefore, it`s important to pay enough attention to the young athletes and their coaches to prevent any manifestations of aggressiveness from their performers and to encourage them to play fair-play sports